Penguatan Literasi Kesehatan Kulit Dan Kemandirian Ekonomi Komunitas Perempuan Dalam Mitigasi Melasma Di Kawasan Pedesaan Gianyar - Putu Shinta Widari Tirka (Jurnal Pengabdian Kepada Masyarakat, 2026)
Melasma is a chronic hyperpigmentation disorder characterized by dark patches on the face caused by ultraviolet (UV) exposure. This condition is common among women in rural areas with high outdoor activity, including a women’s community in Banjar Geria, Gianyar. The main problems include low skin health literacy, unsafe skincare use, and limited financial management for health needs. This community service program aims to enhance participants’ capacity in melasma prevention through skin health education and basic financial management training. The methods include participatory education, skincare application demonstrations, and distribution of educational materials. The results indicate improved understanding of melasma risk factors, better ability to select safe skincare products, and increased awareness of budgeting for health needs. This integrative approach effectively promotes preventive behavior changes and contributes to improving the overall quality of life in the community.